Possession : cognitive sources, forces, and grammaticalization - Heine, Bernd, 1939- (Cambridge studies in linguistics, 1997)
In this new work, Bernd Heine claims that the structure of grammatical categories is predictable to a large extent once we know the range of possible cognitive structures from which they are derived. The author uses as his example the structure of predicative possession, and shows how most of the possessive constructions to be found in the world's languages can be traced back to a small set of basic conceptual patterns. Heine identifies these patterns, and using grammaticalization theory he describes how each affects the word order and morphosyntax of the resulting possessive construction. He argues that grammaticalization theory explains much of the observable typological diversity which characterizes 'have'-constructions in the world's languages. Illustrated by a wealth of examples, this is an original and important statement from a leading linguist.